The communication as base of interpersonal relationship nurse-patient in the care in unit of ready attendance- preview note - Oliveira, Thalita Rocha; Simões, Sonia Mara Faria (Online Brazilian Journal of Nursing, 2010)
One is about a dissertação project of the Academic Master in Sciences of the Health in Care of the Fluminense Federal University, whose objective is to analyze the interpersonal relationship established between nurse and patient in the care of nursing. It is a study of descriptive character with qualitative boarding to be carried through in the Unit of Ready Attendance 24h, pertaining to the Secretarial of Health and Civil Defense of the State of Rio de Janeiro, located in the city Belford Roxo. The subject will be the military nurses who work in this unit. It is intended to bring contributions for the assistance of nursing by means of the sensitization of the professionals on the importance of the interpersonal relations as base for the care in nursing.